Mosquito Nests Eradication through Monitoring the Mosquito Larva (Jumantik) by School Children in Preventing the Dengue Hemorrhagic Fever - Nuurhidayat Jafar; Nur Fadilah; Silvia Malasari; Moh Syafar Sangkala; Andina Setyawati; Andi Wahyuni (Universitas Hasanuddin, 2019)
Background: Dengue Hemorrhagic Fever (DHF) is still a major health problem in Indonesia. Community participation is a key component of DHF control. The group of schoolchildren is part of a group of people who can play a strategic role, considering the number is very much around 20% of the population. Through this Jumantik, the elementary school children are trained as a mosquito larva (jumantik) in their school.   Objective: Establishment of larva monitoring group (Jumantik) and implementation of mosquito nest eradication activity at home and at school   Method: A community service activity is conducted by recruiting and providing the training for Jumantik School Children and the teachers. Before the training, the students were given with the pre-test. After the training, the students followed the post-test and were given the mosquito eradication kit to undertake the mosquito larva monitoring at school and home.   Result: As much as nine elementary students and three teachers were formed as jumantik volunteers from three different elementary schools namely Malewang, Palleko and Pangembang . The result of pre-test of 9 students, the average score of 8.67 (maximum points 15) with the highest score 11 and the lowest score 6. While the post test results obtained an average value of 11, 89 with the highest value 14 and the lowest value 10. The forms of activity for this program were: establishment of Jumatik school children, distribution of mosquito eradication kit, distribution of leaflet and stickers as the media of health promotion, provision of certificate of training of Jumantic school children and the teachers, the establishment of Plan of Action (POA) of the program and the production of second-hand good products.   Conclusion and Suggestion: There are six activities that was implemented in this community service activity. It is suggested that the school to carry out routine activities according to the POA that has been agreed and the community health center can supervise the activity undertaken by the Jumantik school children.   Keywords: Jumantik, Dengue Hemorrhagic Fever, school children, mosquito eradication